Gathering blue - Lowry, Lois. (New York : Dell Laurel-Leaf, 2002)
Lame and suddenly orphaned, Kira is mysteriously removed from her squalid village to live in the palatial Council Edifice, where she is expected to use her gifts as a weaver to do the bidding of the all-powerful Guardians.
"Readers circle"--Cover.
Includes reader's guide.
School Library Journal starred.
Wilson's Children.
Wilson's Junior High School.
5.5
Keywords: Orphans -- Fiction; People with disabilities -- Fiction; Science fiction; Orphans -- Fiction; Physically handicapped -- Fiction; Science fiction